Evaluación del poder de predicción de las expectativas de inflación de los consumidores en México - José Antonio Murillo; Paula Sanchez Romeu (Banco de México, 2012)
– This paper introduces an indicator of consumers' inflation expectations based on data from the National Consumer Confidence Survey of Mexico (ENCO, in Spanish), and tests its predictive power over CPI inflation and other measures of inflation that correspond to smaller baskets of consumer goods, for periods that range from 1 to 12 months. Our findings show that between January 2003 and September 2010, the predictive capability of the indicator over the different measures of inflation used was weak. Due to a modification in the survey questionnaire in October 2010, as of that date we observe a significant change in the responses and, thus, in the behavior of the indicator of consumers' inflation expectations. For this reason, from October 2010 on the main use of this indicator is to be a reference of consumers' confidence in price stability.
Keywords: C14; E31; E58; 330; CPI inflation; consumers' inflation expectations; household surveys; consumer surveys; consumer confidence surveys; ENCO; Verbraucherpreisindex; Inflationserwartung; Verbraucher; Mexiko